城市环境与人类行为：向历史和本土智慧学习 (Urban Environment and Human Behavior: Learning from History and Local Wisdom) - Widodo, Johannes (Academy of Arts & Design of Tsinghua University, 2022)
Zhuangshi - Chinese Journal of Design